Monitoring and Indentification Packet in Wireless with Deep Packet Inspection Method - Ahmad Fali Oklilas; Tasmi Tasmi (Proceeding of the Electrical Engineering Computer Science and Informatics, 2016)
Layer 2 and Layer 3 are used to make a process of network monitoring, but with the development of applications on the network such as the p2p file sharing, VoIP, encrypted, and many applications that already use the same port, it would require a system that can classify network traffics, not only based on port number classification. This paper reports the implementation of the deep packet inspection method to analyse data packets based on the packet header and payload to be used in packet data classification. If each application can be grouped based on the application layer, then we can determine the pattern of internet users and also to perform network management of computer science department. In this study, a prototype wireless network and applications SSO were developed to detect the active user. The focus is on the ability of open DPI and nDPI in detecting the payload of an application and the results are elaborated in this paper.